The ontogenetic development of the somatic musculature of the trunk of the aglossal anuran Xenopus laevis (Daudin) - Ryke, P. A. J.(Pieter Abraham Johannes) (Stellenbosch : Stellenbosch University, 2012)
Originally presented as the author's thesis (D. Sc. -- University of Stellenbosch, 1952).